Utilização do CO2 em substituição ao O2 na ativação de Cu-MAZ na oxidação do metano a metanol - Pereira, Tássia Caroline Passos (2022)
Converting methane to methanol has been a challenge for decades due to the high reactivity of methanol compared to methane. One of the challenges of this reaction to take it to an industrial scale was to find a safer oxidant than those that were used based on molecular oxygen and that it does not decrease the methanol production of the catalyst due to the replacement of the oxidant. In this work it was demonstrated that using Cu-MAZ catalysts O2 can be replaced by CO2, thus creating a process free of molecular oxygen, and consequently safer. The in-situ UV-vis technique and Density Functional Theory Calculation were used to identify the active species in the Cu-MAZ catalysts. The methodology used made it possible to identify the species that react with CH4 under different activation conditions. Activation with inert (He) allowed to identify the presence of a small fraction of active species of the [Cu3O3]2+ type. When investigating the species that reacted with CH4 after activation with O2 or CO2, it was concluded that the main active species in Cu-MAZ catalysts is the 2[CuOH]+ type. CO2 was able to reoxidize Cu+ from the [Cu3O3]2+ species, but did not reoxidize Cu+ generated from the 2[CuOH]+ species. These Cu+ species are reoxidized by H2O above 200 °C, and for the activity of the material to be fully reestablished, a heat treatment with an oxidizing gas that can be CO2 instead of O2 is necessary. At high temperature, CO2 was also able to desorb methanol from the active sites. The use of CO2 in the activation of Cu-MAZ catalysts resulted in a higher productivity of methanol than when using O2, and still allows a modulated process to be carried out by alternating the reactants in the reactor feed without any safety risk.